Breeding system and spatial isolation from congeners strongly constrain seed set in an insect-pollinated apomictic tree: Sorbus subcuneata (Rosaceae) - Hamston, Tracey J. (Sci Rep, 2017)
In plants, apomixis results in the production of clonal offspring via seed and can provide reproductive assurance for isolated individuals. However, many apomicts require pollination to develop functional endosperm for successful seed set (pseudogamy) and therefore risk pollination-limitation, particularly in self-incompatible species that require heterospecific pollen. We used microsatellite paternity analysis and hand pollinations to investigate pollen-limitation in Sorbus subcuneata, a threatened endemic tree that co-occurs with its congener, S. admonitor. We confirmed that S. subcuneata is an obligate pseudogamous apomict, but open-pollinated flowers rarely produced seed (flower-to-seed conversion < 1%) even though they rapidly accumulated pollen on their stigmas. Manual heterospecific pollination by S. admonitor resulted in a high flower-to-seed conversion rate (65%), however, we estimate that the ratio of self: heterospecific pollination in open-pollinated flowers was at least 22:1. Despite the efficacy of heterospecific pollination, the contribution of S. admonitor trees to paternity in seed from open-pollinated flowers of S. subcuneata decreased rapidly with the spatial separation between paternal and maternal trees. Conservation efforts aimed at maintaining species with this breeding system must therefore manage the congeners in tandem which will also maintain the potential for rare heterospecific fertilisation that typically cause rapid diversification in these lineages.